Ontem eles jogaram, hoje é a gente professora : os lugares das meninas na educação física e na escola - Matos, Noelle Thais de (2020)
This work had as general objective to investigate the places that girls-women occupy at Escola Estadual Pedro Gardés and in Physical Education classes in the final years of elementary school, how they are perceived and shown in the institution, their different attitudes, values, prejudices and gestures, because understanding these aspects makes it possible to broaden the look at femininities in society, as they mark their social relations, domination, rules, among others, and thus corroborate with gender studies and the right to learn. The specific objective was to understand which places they appropriate / empower in the school routine, showing themselves as protagonists or not during breaks and in Physical Education classes. The empowerment of girls-women in the educational environment in contemporary times is admitted as different from the past, as there is an opening for gender discussions and expansion of guarantees of rights, contrary to what happened. However, there are gaps to be overcome with regard to gender equity in various fields of our society. To that end, Guacira Louro, Joan Scott and Judith Butler were used as a theoretical basis for gender studies; Erika Moreira, Yi Fu Tuan and Michel Certeau for the study of daily life and the place; Pierre Bourdieu and Michel Foucault for a historical understanding of power relations; Silvana Goellner and Helena Altmann as support for gender issues in School Physical Education. The research with a qualitative approach, of an ethnographic type in the school routine, had as sources and research instruments, the analysis of documentary sources, participant observation, bimonthly Physical Education plan and the semi-structured interview with the focus group technique and brainstorming. The research took place at Escola Estadual Pedro Gardés, located in the center of Várzea Grande City - MT. Participants were elementary school students from the morning shift. The results indicate that in the break time the places that involve games, mainly the sports court, are mainly occupied by boys, even though part of the girls recognize their rights to enjoy these school spaces and claim these rights. It is also noteworthy that in Physical Education classes, the content about invasion sports, with co-educational methodological direction, had an equivalent participation of both girls and boys, but it is worth mentioning the intensity and superior competitiveness of boys in games. The work points out that the appropriation of girls and boys in places is a historical-social construction, mainly of the sports court - used in classes with equal rights from the pedagogical intervention of the teacher and the need for the boys' permissiveness for them to play at times of breaks. In this sense, it is necessary to broaden the views of educators with regard to the appropriation of places in this environment, to encourage the involvement of all with the insertion of the diversification of Physical Education classes from different cultures, to deepen in research that contributes to reflections on female empowerment in the face of the use of the “instituted” spaces of the school in a protagonist way, so as to envision the guarantee of the learning rights to all and everyone.